Thermodynamics of egg production, development and hatching in trematodes. Issue 3 (6th May 2016) - Morley, N.J.; Lewis, J.W.
Abstract: Temperature is a key factor influencing the rate of biological processes of ectothermic animals and is intrinsically linked to climate change. Trematode parasites may be potentially susceptible to temperature changes and, in order to develop a predictive framework of their response to climate change, large-scale analyses are needed. In particular, the biology of the egg of all species is at some time influenced by environmental conditions. The present study uses Arrhenius activation energy ( E* ), a common measure of temperature-mediated reaction rates, to analyse experimental data from the scientific literature on the effects of temperature on the production, development and hatching of trematode eggs. Egg production declines at high temperatures, with habitat-specific climatic factors determining the optimal thermal range. Egg development, as is typical of invertebrates, shows a simple response to temperature, with minimal differences between mid- (35–60°) and low-latitude (<35°) species. Egg hatching demonstrates variable thermodynamics with high E* values at low temperature ranges and thermostability at mid-temperatures, before declining at high temperature ranges, with wide thermostable zones being a common feature. Comparisons between development and hatching indicate that these two parameters demonstrate different thermodynamical responses. The significance of these results in furthering our understanding of trematode egg biology under natural conditions is discussed.